Representation of the use of Media and Teaching Materials in Science Learning for Junior High School Students - Yuni Pantiwati; Fendy Hardian Permana; Aminudin Aminudin; Endrik Nurrohman; Tasya Novian Indah Sari (Postgraduate, University of Mataram, 2024)
Media and teaching materials that suit learning needs can improve the quality of learning. The research aims to describe the use of media and teaching materials in science learning. The type of research is a survey. Research in June-September 2023 at Middle Schools in the Greater Malang Region. The research population was junior high school students and teachers in the Greater Malang area. The research sample was 584 students and 18 teachers. The data collection technique uses a media and learning material needs analysis questionnaire. The research instrument is a needs analysis questionnaire sheet. Data was analyzed descriptively, quantitatively, and qualitatively. The research results show that the media and teaching materials used by teachers are quite good, but teachers rarely use a variety of media and teaching materials. The learning media that teachers often use are learning videos and the teaching materials that are often used are textbooks. Science learning still requires supporting media and teaching materials, one of which is expected to be an e-module